2007
DOI: 10.1177/0883073807307094
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Lateral Rectus Palsy Following Resection of a Pineal Cyst in Sitting Position: Direct or Indirect Compressive Phenomenon?

Abstract: A rare case of delayed lateral rectus palsy in a patient following resection of a pineal lesion in the sitting position is presented. Postoperative pneumocephalus is common following craniospinal surgical intervention in the sitting position. The sixth cranial nerve is frequently injured because of its prolonged intracranial course. A 13-year-old girl was evaluated for unremitting headaches. No focal deficits were demonstrated on neurological examination. Magnetic resonance imaging revealed a cystlike pineal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In a surgical series of 11 patients with pineal cysts, Fetell et al 19 found that patients with headaches can be expected to have postoperative symptomatic relief only if the headaches were caused by hydrocephalus. Although there are reports of surgical treatment of pineal cysts for the treatment of chronic headaches, 20,23,29,62 we do not regard a history of chronic headache in the absence of hydrocephalus as an indication for surgical treatment of a pineal cyst at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…In a surgical series of 11 patients with pineal cysts, Fetell et al 19 found that patients with headaches can be expected to have postoperative symptomatic relief only if the headaches were caused by hydrocephalus. Although there are reports of surgical treatment of pineal cysts for the treatment of chronic headaches, 20,23,29,62 we do not regard a history of chronic headache in the absence of hydrocephalus as an indication for surgical treatment of a pineal cyst at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Stevens et al reported a 13-year-old girl who developed unilateral lateral rectus palsy postoperatively following resection of a pineal cyst in the sitting position [4]. Interestingly, her symptoms of an isolated sixth nerve palsy developed four days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial air along the course of a cranial nerve can result in isolated cranial nerve palsy from direct compression. A review of the literature revealed only three reports of isolated, single cranial nerve deficits due to pneumocephalus [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Although there are reports of pineal cyst surgery performed for the treatment of chronic headaches, 119,122,126,127 most surgeons do not regard a history of chronic headache in the absence of hydrocephalus as an indication for surgical treatment of a pineal cyst. Not surprisingly, headaches can be expected to have reliable postoperative symptomatic relief only if the headaches were caused by hydrocephalus.…”
Section: Pineal Cystsmentioning
confidence: 99%